Multidimensional systems, signal processing algorithms and application techniques - Leondes, Cornelius (Academic Press, 1996)
Praise for the Series. "This book will be a useful reference to control engineers and researchers. The papers contained cover well the recent advances in the field of modern control theory.". --IEEE Group Correspondence. "This book will help all those researchers who valiantly try to keep abreast of what is new in the theory and practice of optimal control.". --Control.